2007
DOI: 10.1111/j.1365-3040.2007.01766.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokinins in responses to water deficit in tobacco plants over‐expressing trans‐zeatin O‐glucosyltransferase gene under 35S or SAG12 promoters

Abstract: The impact of water deficit progression on cytokinin (CK), auxin and abscisic acid (ABA) levels was followed in upper, middle and lower leaves and roots of Nicotiana tabacum L. cv. Wisconsin 38 plants [wild type (WT)]. ABA content was strongly increased during drought stress, especially in upper leaves. In plants with a uniformly elevated total CK content, expressing constitutively the trans-zeatin O-glucosyltransferase gene (35S::ZOG1), a delay in the increase of ABA was observed; later on, ABA levels were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
88
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(106 citation statements)
references
References 40 publications
11
88
2
5
Order By: Relevance
“…Consistent with our finding, Havlová et al (2008) detected an increase in ABA levels in the CK-overproducing 35S:ZOG1 plants under nonstressed conditions. It is possible that an increase of ABA:CK ratio caused by CK deficiency might result in constitutive stomatal closure under well-watered conditions, leading to reduced transpiration, which inhibits CO 2 uptake and thereby negatively impacts photosynthesis (Cornic and Fresneau, 2002).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with our finding, Havlová et al (2008) detected an increase in ABA levels in the CK-overproducing 35S:ZOG1 plants under nonstressed conditions. It is possible that an increase of ABA:CK ratio caused by CK deficiency might result in constitutive stomatal closure under well-watered conditions, leading to reduced transpiration, which inhibits CO 2 uptake and thereby negatively impacts photosynthesis (Cornic and Fresneau, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…threshold also caused stunted plant growth, abnormal tissue development, and sensitivity but not tolerance to drought (Li et al, 1992;Hewelt et al, 1994;Wang et al, 1997;Synkova et al, 1999;Havlová et al, 2008). Therefore, appropriate manipulation of CK levels is necessary to increase leaf longevity and photosynthetic capacity under drought stress, taking into account the dosage effect of CKs on plant growth and stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current studies show that bioactive CK content was reduced by water stress in sugarcane (Table 5-4). This is in line with reports in various plant species which demonstrated a reduction of biosynthesis, metabolism, perception and signal transduction of CK in response to environmental stress (Argueso et al, 2009, Nishiyama et al, 2011, Schachtman and Goodger, 2008, Havlova et al, 2008. However, during the experiment, simultaneously with the development of stress levels, P RAB17 ::IPT plants produced substantially more bioactive CKs than wild-type plants.…”
Section: Discussionsupporting
confidence: 77%
“…However, the hormone analysis results showed that levels of free auxin (indole-3-acetic acid, IAA) were elevated in all plants under water stress conditions. The increase in IAA content was higher in severely stressed leaves of P RAB17 ::IPT than wild-type plants, a finding consistent with the increased bioactive CK and IAA in drought-affected tobacco (Havlova et al, 2008). The P RAB17 ::IPT finding in sugarcane is in line with Bertell and Eliasson (1992) who detected increased in IAA content when CK (6-benzyladenine) was applied to pea plants.…”
Section: Discussionsupporting
confidence: 72%